The The Interpersonal Meaning of Verbal Text and Visual Image Relation in English Textbook for Junior High School Grade VIII - Dewi, Annisa Kumara; Rukmini, Dwi; Saleh, Mursid (Universitas Negeri Semarang, 2020)
This study aimed at explaining the relations between verbal text and visual image in English Textbook for Junior High School Grade VIII in terms of interpersonal meaning. The first is the checklist of verbal text analysis by Halliday in Eggin (2004) to analyse the verbal text. The second is the checklist table for visual image analysis by applying the theory of Kress and Van Leeuween (2006). The last is about the relation between verbal text and visual image in terms of interpersonal meaning (Royce’s theory; 2007). The findings show mostly every chapter is dominated by declarative sentences. In declarative mood, the sentence indicates to state something or explain something. Some conversations indicate the image acts and the gazes of them are ‘offer’, they could be explained that the images address us indirectly, the viewer is not the object, but the subject looked. The represented participants are the object of the viewer’s dispassionate scrutiny, no contact between the viewer and the represented participants. The image acts and the gazes happen between represented participants and represented participants. The eye contacts prove the verbal text produced by the represented participants. Verbally, the statement and question relate through intersemiotics reinforcement of address. The activities between represented participant and represented participant happen verbally in which the viewer do not joint in the conversation. As visually, the eyeline just happened between represented participant and represented participant without the viewer. It could be said relationship happened when the verbal text supports the visual image.